A gospel of irresolution: Illness, trauma, and getting to hope. Issue 4 (24th January 2023) - Thompson, Deanna A.
Abstract: Our tellings of the Christian story often bend toward resolution while the plots of so many of our lives stubbornly resist it. If theologies and religious communities that embody them are going to be places where those who live with serious illness are able to held and supported in ways that mitigate some of their suffering, they need to be spacious enough to hold the grief, trauma, and temptations to despair that accompany those who are seriously ill. One way to do this is to take on the central Christian plotline—the one about death being transformed into new life, the one that bends toward resolution—and let it breathe. This essay begins with one story of what it is like to be undone by cancer, highlighting ways in which the lens of trauma helps illumine the depths of the challenges faced by those who are seriously ill. It then proposes how a gospel of irresolution can be good news to those undone by illness and other awfulness.